Optimization of the Distribution Network Using an Emerging Technology - Ulin Hernández, Emanuel Jesús; Saucedo Martínez, Jania Astrid; Marmolejo Saucedo, José Antonio (2020)
Unmanned Aerial Vehicles (UAVs) are a technology that has recently been incorporated in the distribution of products, which in this study, are packages. It can improve the distribution system in environments where there is significant traffic congestion. Furthermore, UAV can help to deliver small packages between warehouses, by using them as an alternative means of distribution. The incursion is of an emerging technology, in this case the use of drones, for a new delivery system in order to improve a university distribution system, in the view of the fact that in recent years, companies have focused on the use of logistics operations for the improvement of productivity and delivery times. The study presents a mathematical model, based on the Problem of the Traveling Salesman (TSP) for the planning of a route to increase the efficiency in the distribution process at Ciudad Universitaria, an Universidad Autónoma de Nuevo León (UANL) campus that contemplates the use of the emerging technology of UAVs, and the traditional method of using trucks. The model considers restrictions on the use of drones, such as the limitation of travel times and maximum distance.